2021
DOI: 10.1039/d1an00116g
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive electrochemical microRNA-21 biosensor based on intercalating methylene blue signal amplification and a highly dispersed gold nanoparticles/graphene/polypyrrole composite

Abstract: Numerous clinical studies suggest that microRNAs (miRNAs) are indicative biomolecules for the early diagnosis of cancer. This work aims to develop a cost-effective and label-free electrochemical biosensor to detect miRNA-21,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…The peak current of the MB redox process, which was proportional to the miRNA-21 concentration on the electrode surface, was monitored via differential pulse voltammetry (DPV). The new biosensor showed a linear range from 1.0 fM–1.0 nM with a LOD of 0.020 fM, with good selectivity, high stability, and satisfactory reproducibility [ 49 ].…”
Section: Outcomementioning
confidence: 99%
“…The peak current of the MB redox process, which was proportional to the miRNA-21 concentration on the electrode surface, was monitored via differential pulse voltammetry (DPV). The new biosensor showed a linear range from 1.0 fM–1.0 nM with a LOD of 0.020 fM, with good selectivity, high stability, and satisfactory reproducibility [ 49 ].…”
Section: Outcomementioning
confidence: 99%
“…Therefore, MB is often employed for sensitive electrochemical detection of microRNA due to its signal amplification properties. For instance, an electrochemical sensor modified using graphene, polypyrrole, and gold nanoparticles was applied for the detection of miR-21 based on intercalating MB signal amplification [49]. The peak current of MB redox process was proportional to miR-21 concentration, achieving low detection limit of 0.02 fM.…”
Section: Intercalation Of Redox Mediatormentioning
confidence: 99%
“…For example, Pothipor et al demonstrated an increase in sensing performance by introducing small amounts of polypyrrole in a microRNA electrochemical sensor. [ 13 ] Thin films of polypyrrole have been used as supports for enzymes for their adsorptive properties. [ 14 ] If the load of polypyrrole is relatively high, it can increase the capacitance of the electrode, which can be useful for different electronic devices.…”
Section: Introductionmentioning
confidence: 99%